Discovery and reminiscence : essays on the poetry of Mona Van Duyn - Burns, Michael, 1953- (University of Arkansas Press, 1998)
"A former United States Poet Laureate, winner of a Pulitzer Prize, and recipient of numerous grants and awards, Mona Van Duyn has been hailed as one of our greatest living American poets. To help broaden and uniquely inform our understanding of Van Duyn's work, editor Michael Burns has gathered ten essays, a poem, a succinct biographical sketch, and Van Duyn's own Laureate address to the Library of Congress."--BOOK JACKET.